Herbicide tolerance of maize genotypes in the wet 2016 year - Bónis, Péter; Árendás, Tamás; Sugár, Eszter; Szőke, Csaba; Darkó, Éva; Marton, L. Csaba (Acta Agraria Debreceniensis, 2017)
The herbicide tolerance levels of 49 Martonvásár inbred parents were examined in Martonvásár in a herbicide susceptibility trial in 2016. The normal dosage recommended in the permit documentations and double dosage were used for the 12 small-plot herbicide treatments performed in two repetitions. Spraying of early post-emergent herbicides was carried out in the 1–2-leaf stage, while post-emergent treatments were applied in the 7–8-leaf stage of maize. The extent of phytotoxicity was scored for the early post-emergent herbicides two and four weeks after treatments and for the post-emergent herbicides two weeks after treatments, respectively. Some of the herbicides examined are not approved in seed production; however it is important to know the reaction of maize parent genotypes for every type of herbicides. The active agent topramezone was withdrawn from the market in 2015, but it was included in the trials as its usage was allowed until stocks run out in 2016. The herbicide agents were examined as follows: mesotrione + S-metolachlor + terbutylazine; isoxaflutol + tiencarbazon methyl + cyprosulfamide; isoxaflutol + cyprosulfamide; mesotrione + terbuthylazine; tembotrione + isoxidifen-ethyl; mesotrione + nicosulfuron; prosulfu ron; nicosulfuron +prosulfuron + dicamba; bentazone + dicamba; nicosulfuron; topramezone; foramsulfuron + isoxadifen-ethyl.Among early post-emergent herbicides, isoxaflutol + cyprosulfamide caused the less phytotoxic damage in the genotypes. The large amount of precipitation during the spring facilitated the infiltration of the active ingredient S-metolachlor, used regularly and successfully also in seed production, into the root zone, resulting in phytotoxic symptoms on susceptible inbred lines at the time of the first inspection. These genotypes recovered by the end of the vegetation period. The spring weather was cooler than usual, retarding the development of maize and thus led to the slower fermentation of herbicide active ingredients, accordingly, all of the post-emergent herbicides caused visible phytotoxic symptoms on some of genotypes. The most severe damages were generally caused by the double dosage of nicosulfuron + prosulfuron + dicamba, nicosulfuron, and foramsulfuron + isoxadifen-ethyl.